Aftermath of topiramate: An interesting case report and literature review - Vijayalakshmi A Senthilkumar; Sharmila Rajendrababu (TNOA Journal of Ophthalmic Science and Research, 2019)
We report an interesting case report on idiosyncratic reaction of topiramate causing bilateral secondary acute angle-closure glaucoma with glaukomflecken, which mimicked acute primary angle closure (APAC) with nongranulomatous uveitis and choroidal effusions. After conservative management, signs and symptoms stabilized within 72 h, but the patient developed posterior synechiae with intermittent peripheral anterior synechiae (PAS) in BE, which was more prominent in LE. Here we report this case because presentation of topiramate-induced idiosyncratic reaction with glaukomflecken and subsequent resolution with posterior synechiae and PAS were rarely documented in literature. A detailed history taking and meticulous clinical evaluation helped us differentiate from APAC.